Instructional leadership in Malaysia: a review of the contemporary literature - Harris, Alma; Jones, Michelle; Adams, Donnie; Cheah, Kenny (Taylor & Francis, 2019)
This article provides a review of the contemporary instructional leadership research base in Malaysia. The core aim of this review is to assess the recent knowledge base on instructional leadership in Malaysia and to evaluate its current contribution to the existing international literature. The article explores a range of published material that has focused explicitly on instructional leadership and instructional leadership practices in Malaysia, including that written in Bahasa Malaysia. The article outlines the findings from the review and highlights certain strengths and limitations. The article concludes by identifying areas for further enquiry and investigation.